1988
DOI: 10.1002/bbpc.198800038
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in Dialkylammonium Chlorides. An Adiabatic Calorimetry Study

Abstract: Alkylammonium Salts / Phase Transitions / ThermodynamicsThe heat capacities of four di-n-alkylammonium chlorides (di-n-pentylammonium chloride, di-n-hexylammonium chloride, di-n-octylammonium chloride, and di-n-decylammonium chloride) were measured from T = 25 K to 350 K using adiabatic calorimetry. All of the compounds investigated were observed to undergo solid-solid phase transitions in the temperature region examined. The thermodynamic properties obtained for these compounds were compared with those of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Interestingly, the molar Δ S tr of (C 6 ) 2 Br (80 J mol –1 K –1 ) is more than twice as large as that of (C 6 H 13 NH 3 ) 2 MnCl 4 (37 J mol –1 K –1 ) even though both compounds undergo transitions near 292 K. This can be partially attributed to a minor disordering transition that (C 6 H 13 NH 3 ) 2 MnCl 4 undergoes at much lower temperatures, though the total hydrocarbon order–disorder transition entropy is still 21% lower for the 2D perovskite compared to (C 6 ) 2 Br. This could result from a gradual change in hydrocarbon degrees of freedom for (C 6 H 13 NH 3 ) 2 MnCl 4 outside of the first-order phase-transition regions or could reflect an intrinsic difference in the overall entropy change that may arise from differences in chain packing and confinement effects …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the molar Δ S tr of (C 6 ) 2 Br (80 J mol –1 K –1 ) is more than twice as large as that of (C 6 H 13 NH 3 ) 2 MnCl 4 (37 J mol –1 K –1 ) even though both compounds undergo transitions near 292 K. This can be partially attributed to a minor disordering transition that (C 6 H 13 NH 3 ) 2 MnCl 4 undergoes at much lower temperatures, though the total hydrocarbon order–disorder transition entropy is still 21% lower for the 2D perovskite compared to (C 6 ) 2 Br. This could result from a gradual change in hydrocarbon degrees of freedom for (C 6 H 13 NH 3 ) 2 MnCl 4 outside of the first-order phase-transition regions or could reflect an intrinsic difference in the overall entropy change that may arise from differences in chain packing and confinement effects …”
Section: Results and Discussionmentioning
confidence: 99%
“…Similar to 2D perovskites, dialkylammonium halides thus feature bilayers of hydrocarbon chains that are confined through hydrogen bonding interactions with 2D sheets of halide anions and can undergo reversible solid-state order–disorder transitions. Although the phase-change thermodynamics of many dialkylammonium halides has been investigated in detail at ambient pressure in the context of thermal energy storage, the structural information available for this class of compounds is limited, making it challenging to gain mechanistic insights into their phase transitions and to establish structure–property relationships. ,, In addition, the effect of pressure on dialkylammonium halide phase transitions has not yet been investigated, though we note a somewhat similar compound (di- n -butylammonium tetrafluoroborate) was recently reported to exhibit large barocaloric effects . Herein, we report a detailed investigation of barocaloric effects in symmetric dialkylammonium halide salts and demonstrate that, when appropriately designed, these materials exhibit properties that make them promising solid refrigerants.…”
Section: Introductionmentioning
confidence: 98%
“…The high entropy in the solid-solid phase transition indicates solid state alkyl-chain melting. It is through the melting of these chains in the solid state that the material is able to absorb energy without actually changing state from solid to liquid (Van Oort et al, 1988). Some of the fundamental material properties of the PCM used for the simulation are tabulated below in…”
Section: Dal Hsm Materials Propertiesmentioning
confidence: 99%
“…The material is available in the form of coarse particles, which can be grounded into a very fine powder, to assist with integration of the PCM into any building material. It possesses excellent solid-solid phase change characteristics in the temperature range of 25 K and 350 K (Van Oort et al, 1988). The adiabatic calorimetry experiments have shown that the phase transition of this PCM occurs at 297.7 K with a molar heat of transition of 16000 J/mol.…”
Section: Dal Hsm Materials Propertiesmentioning
confidence: 99%
“…Approximately 5-25 mg of each sample was measured in a Perkin-Elmer TM Pyris-1 TM DSC with the Cryofill TM temperature control accessory. The system was calibrated for temperature and enthalpy changes with the solidsolid phase transition of dipentylammonium chloride [23] under a flow of, 20 mL min À1 , ultra-dry helium. The heating-cooling method used for the PEO composite samples was as follows: cool from room temperature to À150 C, heat from À150 to 100 C at a scan rate of 10 K min À1 , hold at 100 C for 1 min, cool to À150 C at 10 K min À1 , hold at À150 C for 1 min, heat from À150 to 100 C at a rate of 10 K min À1 .…”
Section: Differential Scanning Calorimetry (Dsc) Of Peo Nanocompositesmentioning
confidence: 99%